Analisis Penguasaan Lahan Petani Sawah Urban dan Keberlanjutan Pertanian Secara Ekologi - Nurdin Mappa; Saleh Molla; Ardi Rumallang (Jurnal Ilmiah Membangun Desa dan Pertanian, 2024)
Land tenure for farmers is very urgent because land is one of the natural resources that is a place to do farming. Without farming land, it isn't easy to carry out. Recently, land tenure for farmers has decreased, and some farmers even have almost no land to work on. One of the components of farmers experiencing a land crisis is farmers living in urban areas, especially those living on the city's outskirts. This study aims to analyze land tenure institutions for urban farmers and the ecological sustainability of agriculture in the Bangkala sub-district, Manggala sub-district, Makassar City. This research lasted for three months, from June 2021 to August 2021. This study used 21 rice field farmers as informants, determined by the snowball method. How does one urban farmer know as a paddy rice manager? So far, he knows enough other urban farmers. They provide information on other farmers who can provide data, and so on, until the researcher gets information on 21 people. This method is used because urban farmers are hard to find. The data is in the form of primary data obtained through saturated or in-depth interviews, namely obtaining the same or repeated answers from informants using interview sheets. In contrast, secondary data is obtained through available documents to support this research, and the data analysis technique used is a qualitative descriptive analysis. The results showed that the total land tenure by farmers was 18.13 hectares, all of whom were cultivators with a land tenure system through leasing or sakap. On average, per farmer only controls 0.86 hectares of land per person. The control of paddy fields is getting narrower. Based on this condition, land tenure by urban farmers in Bangkala Village, Manggala District, cannot be expected to support ecologically sustainable agriculture.